Phosphoproteomic Analyses Reveal Early Signaling Events in the Osmotic Stress Response - E. Stecker, Kelly (American Society of Plant Biologists, 2014)
Elucidating how plants sense and respond to water loss is important for identifying genetic and chemical interventions that may help sustain crop yields in water-limiting environments. Currently, the molecular mechanisms involved in the initial perception and response to dehydration are not well understood. Modern mass spectrometric methods for quantifying changes in the phosphoproteome provide an opportunity to identify key phosphorylation events involved in this process. Here, we have used both untargeted and targeted isotope-assisted mass spectrometric methods of phosphopeptide quantitation to characterize proteins in Arabidopsis (Arabidopsis thaliana) whose degree of phosphorylation is rapidly altered by hyperosmotic treatment. Thus, protein phosphorylation events responsive to 5 min of 0.3 m mannitol treatment were first identified using (15)N metabolic labeling and untargeted mass spectrometry with a high-resolution ion-trap instrument. The results from these discovery experiments were then validated using targeted Selected Reaction Monitoring mass spectrometry with a triple quadrupole. Targeted Selected Reaction Monitoring experiments were conducted with plants treated under nine different environmental perturbations to determine whether the phosphorylation changes were specific for osmosignaling or involved cross talk with other signaling pathways. The results indicate that regulatory proteins such as members of the mitogen-activated protein kinase family are specifically phosphorylated in response to osmotic stress. Proteins involved in 5′ messenger RNA decapping and phosphatidylinositol 3,5-bisphosphate synthesis were also identified as targets of dehydration-induced phosphoregulation. The results of these experiments demonstrate the utility of targeted phosphoproteomic analysis in understanding protein regulation networks and provide new insight into cellular processes involved in the osmotic stress response.